PEMBERDAYAAN KELOMPOK TANI HUTAN GIRI PUSPA MELALUI PELATIHAN PENGELOLAAN WISATA ALAM BERBASIS MASYARAKAT - Wawan Hermawan; Andi Sukandi; Iifan Auchep Venkatanathan (JCI Publisher, 2026)
Community-based nature tourism development is an important strategy for community empowerment that can enhance local economic welfare while supporting environmental sustainability. However, the success of community-based tourism management largely depends on the capacity of human resources and local institutions. This study aims to analyze the role of community-based nature tourism management training in improving individual capacities and strengthening the institutional capacity of the Giri Puspa Forest Farmer Group (Kelompok Tani Hutan/KTH) as the manager of Lembah Puspa Educamp in West Bandung Regency. This research employed a qualitative approach using a case study method. Research informants consisted of the group leader, management board members, KTH members, training facilitators, and tourism development partners selected through purposive sampling. Data were collected through in-depth interviews, observations, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. The findings reveal that the training contributed significantly to improving participants’ competencies in tour guiding, visitor services, tourism safety, environmental interpretation, and digital marketing. Furthermore, the training strengthened institutional capacity through enhanced coordination, task distribution, member participation, and collective decision-making processes. The program also supported the implementation of Community Based Tourism (CBT) principles, as reflected in increased community involvement in tourism management and destination development. Nevertheless, several challenges remain, including limited funding, inadequate supporting facilities, and unequal competency levels among group members. The study concludes that training serves as a strategic instrument for community empowerment and institutional strengthening to support sustainable community-based nature tourism management